Induction of active zones at ectopic neuromuscular junctions in the frog - Ko, CP (J Neurosci, 1989)
To examine de novo differentiation of the active zone, ectopic neuromuscular junctions were studied in adult frog muscles. Ectopic junctions induced by excising the original endplate region and implanting the nerve to an endplate-free site were examined by light and electron microscopy 4 weeks-1 year after operations. The earliest time point at which ectopic junction formation was detected with freeze fracture was 6 weeks postoperation, when clusters of active zone particles were observed scattered across the nerve ending. Subsequently, short active zones (6–10 weeks postoperation, length mean = 0.36 +/- 0.24 microns) composed of the characteristic 2 double rows of particles are detected. Before junctional folds are observed with freeze fracture, many active zones are parallel to each other and to the long axis of the nerve. The average angle 6–10 weeks postoperation is 27 degrees +/- 23 degrees. Even during these early stages of formation, active zones are functional. As time passes, active zones attain a more typical, perpendicular orientation (12–18 weeks postoperation, mean = 62 degrees +/- 24 degrees) and also increase in length (mean = 0.69 +/- 0.45 microns). However, even after 1 year, the orientation (angle, mean = 70 degrees +/- 22 degrees) and the length (mean = 0.78 +/- 0.63 microns) of active zones at ectopic junctions are still not well correlated with active zones at normal junctions (normal active zone angle mean = 85 degrees +/- 5 degrees, length mean = 1.00 +/- 0.57 microns).(ABSTRACT TRUNCATED AT 250 WORDS)